Vitamin D Deficiency and Supplementation in Irritable Bowel Syndrome: Retrospective Evaluation of Subtype and Sex-Based Differences - Nur Düzen Oflas; Yonca Yılmaz Ürün (Medicina)
Background and Objectives: Irritable bowel syndrome (IBS) is a prevalent functional gastrointestinal disorder with diverse subtypes. Recent evidence has suggested a link between vitamin D deficiency and IBS; however, the associations between vitamin D levels, IBS subtypes, and hematological–biochemical parameters remain unclear. The aim of this research was to investigate the associations between vitamin D status, IBS subtypes, and sex, along with their relationships with biochemical and hematological parameters. Materials and Methods: This retrospective study included 240 patients diagnosed with IBS according to the Rome IV criteria at Van Yüzüncü Yıl University Medical Faculty Hospital. The patients were classified as diarrhea-predominant (IBS-D), constipation-predominant (IBS-C), or mixed-type (IBS-M). The patients’ serum vitamin D levels and hematological (hemoglobin, white blood cell and platelet counts, and mean corpuscular volume) and biochemical (ferritin, iron, calcium, magnesium, and vitamin B12 levels) parameters were evaluated at baseline and after vitamin D supplementation. Sex-related differences were assessed. Results: Baseline vitamin D levels were low in all IBS subtypes, with no significant differences between the groups. Vitamin D supplementation resulted in a significant increase in serum vitamin D levels across all subtypes (p = 0.001). No significant correlations were identified between vitamin D levels and hematological or biochemical parameters. Sex differences in vitamin D levels were only significant in the IBS-M group, both at baseline and post-treatment (p < 0.05). Conclusions: Vitamin D deficiency is prevalent among all IBS subtypes and significantly improves with supplementation, independently of the subtype. Although no associations were found between vitamin D levels and laboratory parameters, the observed sex differences in patients with IBS-M highlight the need for further research into potential sex-related pathophysiological mechanisms. These findings support the integration of routine vitamin D assessment and supplementation into the clinical management of IBS, especially in patients with the IBS-M subtype and female sex, to potentially improve patient outcomes.